2016
DOI: 10.1248/cpb.c15-00903
|View full text |Cite|
|
Sign up to set email alerts
|

DNA Interaction and Cytotoxicity of Cyclometalated Ruthenium(II) Complexes as Potential Anticancer Drugs

Abstract: To evaluate the anticancer activity of the cyclometalated ruthenium(II) complexes [Ru(bpy) 2 (C^N)]Cl, we have studied the interaction of these complexes using calf thymus DNA (CT-DNA) and cytotoxicity assays with two tumor (L1210 and HeLa) and a non-tumor (BALB/3T3 clone A31) cell lines. It is suggested that the complexes act as intercalators and/or DNA minor groove binders. Moreover, the complexes display favorable cytotoxicity activities with L1210 and HeLa, which in all cases were significantly more favora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 38 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…CD and UV experiments revealed DHA analogs bind to DNA via intercalation and fluorine analogs act as intercalator as well as minor groove binder. Nakabayashi et al reported three cyclometalated ruthenium(II) complexes [Ru(bpy) 2 (C^N)]Cl 104 – 106 in order to study their ct-DNA binding affinity and cytotoxicity against two tumor (L1210 and HeLa) and a non-tumor (BALB/3T3 clone A31) cell lines [ 186 ]. Conjugates 104–106 primarily act as intercalators and/or minor groove binders.…”
Section: Reviewmentioning
confidence: 99%
“…CD and UV experiments revealed DHA analogs bind to DNA via intercalation and fluorine analogs act as intercalator as well as minor groove binder. Nakabayashi et al reported three cyclometalated ruthenium(II) complexes [Ru(bpy) 2 (C^N)]Cl 104 – 106 in order to study their ct-DNA binding affinity and cytotoxicity against two tumor (L1210 and HeLa) and a non-tumor (BALB/3T3 clone A31) cell lines [ 186 ]. Conjugates 104–106 primarily act as intercalators and/or minor groove binders.…”
Section: Reviewmentioning
confidence: 99%
“…Billions of dollars are spent annually on research in order to cure or improve the life-standards of the cancer patients. [1][2][3] The traditional cancer treatments, including surgery, radiation therapy and chemotherapy, result in serious adverse effects caused by the loss of the functions of normal organs. 1) Photodynamic therapy (PDT) is a form of phototherapy using nontoxic light-sensitive compounds that are exposed selectively to light, whereupon they become toxic to targeted malignant and other diseased cells.…”
mentioning
confidence: 99%